Menjaga identitas nasional dalam konteks keberagaman budaya Indonesia - Cahyani, Aliyyah May (Maliki Interdisciplinary Journal, 2025)
Indonesia is famous for its extensive cultural variety, which includes a multitude of ethnic communities, regional languages, traditions, and practices. This rich tapestry represents both a valuable advantage and a challenge in fostering a cohesive national identity. The objective of this research is to explore the role of national identity as a unifying element within a landscape of cultural diversity and to develop approaches for its reinforcement. The methodology utilized involves reviewing literature and conducting a descriptive analysis of a range of governmental policies and socio-cultural practices within Indonesia. Findings indicate that fostering nationalism through character education, enhancing digital literacy, promoting the preservation of local cultures, encouraging active participation from families and communities, and implementing inclusive government policies are crucial components in protecting national identity. Collaborative initiatives between the government and societal organizations are vital to transform diversity into a source of unity instead of discord. In summary, maintaining national identity while embracing cultural diversity is essential for establishing a robust, harmonious, and independent Indonesia.